IMPLEMENTASI MEDIA POSTER SESSION UNTUK MENINGKATKAN PEMAHAMAN MATERI PAI SISWA JURUSAN IPA DI SMAI ALMA’ARIF SINGOSARI - Roudhotul Jannah; Anwar Sa’dullah; Arief Aridiansyah (VICRATINA, 2021)
Advance in science and technologi, especially information technology have a great influence on the preparation and implementation of learning strategies. The implementation of poster session media in the subject of Islamic Education is a new challenge of SMA Islam Alma’arif Singosari. The focus of this research is to discuss the understanding of Islamic education material for student, the implementation of the poster session media, and the obstavles to the application of the poster session media. This research uses a qualitative approach with the type of case study research. Data collection is done by data reduction, data presentation, and data verification. The audit of research result is carried out with obsever diligence peer examination, and triangulation. The result of study explain that student understanding Islamic education is quite good, implementation of poster session media has been carried out, but not all Islamic education material can use poster session media, and the main obstacle to using poster session media lies in student discipline in working and the lack of adequate facilities fot student in Islamic Boarding.